Trends in Khmer art - Boisselier, Jean (Studies on Southeast Asia., 1989)
A translation of Professor Boisselier's original work. This monograph discusses twenty-four sculptures representative of Khmer art. Includes brief chapters on the history and religions of Cambodia as background for understanding the discussion of the statuary itself, as well as beautiful black-and-white reproductions and a glossary.